ANALISIS KETERAMPILAN COMPUTATIONAL THINKING CALON GURU SEKOLAH DASAR PADA MATA KULIAH MATEMATIKA DASAR - Istiqomah; Ririn Hestiningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the computational thinking skills of prospective elementary school teachers in basic mathematics courses. The method used in this study is qualitative descriptive research. The research subject semester I students of PGSD Study Program, Harkat Negeri University. The data collection technique used uses skill test instruments in answering math problems in basic mathematics courses with the subject matter of the smallest common multiple and the largest fellowship factor. The collected data were analyzed using a qualitative descriptive approach. After data analysis, it is known that the first and second questions respondents are able to solve problems with components of computational thinking which include decomposition, abstraction, algorithms, and generalization, while there are different components in solving two different problems.